Clinical Dilemma of Positive Histologic Chorioamnionitis in Term Newborn - Cuna, Alain; Hakima, Laleh; Tseng, Yun-An; Fornier, Bianca; Islam, Shahidul; Quintos-Alagheband, Maria Lyn; Khullar, Poonam; Weinberger, Barry; Hanna, Nazeeh (Frontiers in Pediatrics, 2014)
Background: Although histologic chorioamnionitis (HCA) is known to be associated with poor outcomes in preterm infants, its clinical significance among term infants is not clearly known. Objectives: To investigate the utility of HCA in determining early onset clinical sepsis (EOCS) among term newborns. Methods: The incidence of HCA and EOCS in term infants born during 2008-2009 was evaluated in a single-center retrospective study (n = 3417). The predictive value of HCA for determining EOCS in term infants admitted to the NICU for suspected sepsis (n = 388) was quantified. Outcome of otherwise healthy term infants in the nursery with HCA was also investigated. Results: Overall, 11% of term infants with HCA also had EOCS. HCA was associated with increased risk for EOCS (OR 2.6, 95% CI 1.6-4.2, p < 0.001) among term infants admitted to the NICU for suspected sepsis. No cases of EOCS were found among otherwise well-appearing infants in the nursery with HCA. Multiple logistic regression analysis indicated that addition of HCA does not increase the power of a model combining C-reactive protein and immature to total neutrophil ratio in determining EOCS. Conclusions: Although HCA in term infants is associated with EOCS, it didn’t improve the ability of C-reactive protein and immature to total neutrophil ratio to predict EOCS. Routine placental examination may not contribute to the diagnosis of EOCS in term infants.